2011
DOI: 10.4314/sajas.v41i4.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary turmeric supplementation on plasma lipoproteins, meat quality and fatty acid composition in broilers

Abstract: An experiment with 200 day-old male broiler chickens was conducted to investigate the effect of the dietary supplementation of turmeric rhizome powder (TRP) on plasma lipoprotein concentrations, and the meat quality and fatty acid composition of the thigh muscle of the broilers. The four treatments were 0% (F.TRP), 0.25% (L.TRP), 0.50% (M.TRP) and 0.75% (H.TRP) TRP in the diets. The pH and the fat, protein, dry matter and ash concentrations of thigh meat did not show significant differences between treatments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 42 publications
7
19
0
1
Order By: Relevance
“…Both two levels of nanocurcumin used in dietary supplementation increased protein content as compared with Group 2, significantly. Daneshyar et al reported that dietary supplementation with turmeric rhizome powder could not cause any significant differences regarding fat and ash content of broiler thigh meat (Daneshyar, Ghandkanlo, Bayeghra, Farhangpajhoh, & Aghaei, ). As mentioned earlier, coccidiosis can decrease the efficiency of nutrients digestion and absorption (Ruff & Fuller, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both two levels of nanocurcumin used in dietary supplementation increased protein content as compared with Group 2, significantly. Daneshyar et al reported that dietary supplementation with turmeric rhizome powder could not cause any significant differences regarding fat and ash content of broiler thigh meat (Daneshyar, Ghandkanlo, Bayeghra, Farhangpajhoh, & Aghaei, ). As mentioned earlier, coccidiosis can decrease the efficiency of nutrients digestion and absorption (Ruff & Fuller, ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, coccidiosis can decrease the efficiency of nutrients digestion and absorption (Ruff & Fuller, ). Daneshyar et al reported that dietary supplementation with turmeric rhizome powder in broiler chickens could increase the crude protein of broiler thigh meat (Daneshyar et al, ). Curcumin may have digestive stimulant activity due to choleretic action and the ability to increase pancreatic digestive enzymes secretion (Al‐Sultan & Gameel, ; Platel & Srinivasan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Too much fat deposition is also undesirable to consumers who are increasingly concerned with the nutritional quality of food. For these reasons, many studies have recently focused on the lipid-lowering effects of natural compounds added to chicken feed (Kobayashi et al, 2002;Huang et al, 2007;Wongsuthavas et al, 2008;Daneshyar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the highest of serum HDL in the experimental duck supplemented with curcumin at dose of 36 mg/duck/day in the green or blue light indicated that curcumin in monochromatic light involed in the HDL cholesterol metabolism. Moreover, the increase in bioavailability of curcumin can effectively increase the concentration of HDL (Daneshyar et al, 2011;Chandrakala and Tekulapally, 2014;Mirzabeigi et al, 2015).…”
Section: Serum Vldl Ldl and Hdl At Sexual Maturity Of Magelang Ducksmentioning
confidence: 99%